Galvanomagnetic effects in tellurium whiskers. Issue 2 (31st August 2015) - Averkiev, N. S.; Berezovets, V. A.; Savchenko, G. M.; Nikolaeva, A.
Abstract : Galvanomagnetic effects on Te samples were studied. The measurements were made in the broad range of temperatures (1.5 K ≤  T  ≤ 80 K) and the values of the magnetic field induction. Shubnikov–de‐Haas oscillations (SH) were detected in strong magnetic fields ( ω c τ ≫ 1, where ω c is the cyclotrone frequency); as well as anomalous temperature dependence of the Hall potential in classically weak ( ω c τ ≪ 1) magnetic fields. It was found out that the revealed SH oscillations are due to the Landau quantizations of the energy spectrum of three‐dimensional (3D) charge carriers (holes) in the bulk samples under study. In the area of weak magnetic fields ( ω c τ ≪ 1), the effect of anomalous magnetoresistance was found, which was due to the weak localization of 3D holes in the samples1 . The theory of the Hall effect for holes in weak magnetic fields ( B < 0.2 Т) was developed. It is based on the solution of kinetic Boltzmann equation with the specific type of the collision integral; taking into account the carriers energy spectrum in tellurium. It was shown that the peculiarities of the Hall effect temperature dependence; which were found experimentally in weak magnetic fields; can be qualitatively explained if we bear in mind the complex structure of tellurium valence band.